Yarn Winning Machine Design - Joko Santoso (Sean Institute, 2023)
A mop is a very simple tool, but it is very much needed in society, especially to help with household work. In this final project the author tries to make a thread roller to process the manufacture of mops. The basic material for making mops is 0.85 cotton yarn and the waste material is clothing waste. The design of a tool with results that can support the need for the manufacture of basic materials in the production of mops, which is expected to be useful for the textile industry, which can meet market needs and can be used as a home industry so that it can improve people's living standards. In the design of the Yarn Winding Machine above, it can be produced: the diameter of the driving pulley is 100 mm and the diameter of the pulli being driven is 100 mm. The ratio of the pulli on the drive shaft to the pulli being driven is 1: 1, the main shaft of 19 mm can deliver 144 watts of power. These machines have a transmission system driven by an electric motor HP/1400 rpm/1 phase by using a large pulley of 210 mm with a small pully diameter of 45 mm. Belts used with L = 813 mm with a total of 2 pieces can connect a power of 144 watts.